Dampak Rumor Terhadap Volatilitas Harga Saham: Studi Empiris di Bursa Efek Indonesia - Rijanto, Y. Arief (Universitas Prasetiya Mulya, 2010)
«Buy on rumor, sell on news» strategy is common trading strategy done by the investor. This strategy contains a higher risk associated with the change of stock price volatility. This empirical study aims to explore the impact of rumors on stock prices by analyzing the changes in volatility patterns during circulation of rumors. This volatility patterns indicate a change in stock price trend due to rumors. The possibility of stock price movement will occur and turn stock price trend up or down. The volatility patterns that occurred in the general period compared with the rumors period. This study uses intraday stock price data (15-minute) during the 2007-2009 and rumors circulation period. Asymmetric GARCH and Treshold GARCH model is used to analyze an asymmetric or symmetric volatility pattern. Results showed that volatility pattern transformation during rumor circulation is different for different types of stocks. The impact of rumors on each stock is different. Rumors are not always increase stock price volatility and clustering. And the changes in volatility pattern due to rumors do not always trigger the stock price movement (trend) to rises or falls. As the result, the strategy implementation of «buy on rumor, sell on news» will be different for each stock and need to be adjusted with the volatility pattern of each stock (asymmetric or symmetric). It creates more uncertainty and risk. But, it also makes more opportunity in stock abnormal return.